Planar magnetron plasma devices and applications - Villamayor, Michelle Marie S. (National Institute of Physics, College of Science, University of the Philippines Diliman, 2014)
This dissertation has three contributions in the field of dusty plasma and thin films deposition by using planar magnetron plasma sputtering devices. A novel technique was developed in order to observe plasma dust without the need for major modification of the plasma machine. TiO2 was successfully deposited on various substrates without substrate heating making deposition of titania thin film on thermally sensitive materials like cloth possible. Transparent conducting ZnO was fabricated on boro-silicate glass substrates using safe and chemically stable H2O vapor as oxygen source.High dynamic range (HDR) images of plasmas and deposits in a discharge chamber shows the erosion of a graphic target surface inside a compact planar magnetron (CPM) discharge device. The erosion pattern are correlated to the light intensity distribution of the plasma during operation. HDR coupled with colorimetry was able to capture the dust deposition occuring first near the ports towards the evacuation pumps and then spreads at the periphery after several hours of operation. A dual planar magnetron (DPM) configuration featuring a mirror reactive planar magnetron system was able to synthesize light sensitive TiO2 deposited on silicon substrate heated at 320 ℃ - 380 ℃ during deposition. Diffracted intensities show the formation of rutile (220), rutile (110) and anatase (101) polymorphs.Silicon, glass and cotton cloth were deposited with TiO2 using a CPM plasma sputtering device without substrate heating. TiO2 on clot, glass, and glass with silver thin film exhibited photocatalytic degradation of methylene blue. Glass was further functionalized with TiO2 by making it antibacterial (Escherichia coli). TiO2 NPs about 350-400 nm in diameter were synthesized on glass coated with silver. UV fluorescent TiO2 macrocrystals were deposited on silicon. Transparent conducting ZnO was deposited on glass using a D120mm x 80 mm CPM. The gases used were argon and oxygen plasma derived from liquid H2O. For the deposition duration of 3,5, and 7 minutes, the measured film thickness were 21.5 nm, 15 nm and 16 nm, respectively.